2022
DOI: 10.3389/fphar.2022.819551
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Community Pharmacists’ Viewpoints About Pharmacovigilance and Adverse Drug Reaction Reporting in Saudi Arabia

Abstract: This study assessed the knowledge, attitudes, and practices of community pharmacists regarding pharmacovigilance and adverse drug reaction (ADR) reporting system in Saudi Arabia. A cross-sectional survey of community pharmacists from different regions in Saudi Arabia was performed through convenience sampling between November 2020 and January 2021. The responses were received from 1,172 community pharmacists. Most respondents (86.7%) were familiar with the National Pharmacovigilance and Drug Safety Center, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…This is a cross-sectional assessment of the community pharmacists' knowledge, perception, and current practice toward PV and reporting the ADR to the regulatory health authority in Saudi Arabia (National Pharmacovigilance Center (NPC- SFDA)). Similar to the previous studies, the results of this study have demonstrated that community pharmacists have an adequate level of knowledge regarding PV fields 15 , 16 . However, there was a clear gap in their knowledge in relation to the health authority responsible for the collection and analysis of ADR reports in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is a cross-sectional assessment of the community pharmacists' knowledge, perception, and current practice toward PV and reporting the ADR to the regulatory health authority in Saudi Arabia (National Pharmacovigilance Center (NPC- SFDA)). Similar to the previous studies, the results of this study have demonstrated that community pharmacists have an adequate level of knowledge regarding PV fields 15 , 16 . However, there was a clear gap in their knowledge in relation to the health authority responsible for the collection and analysis of ADR reports in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…The community pharmacists in the current study demonstrated positive perceptions of the importance of PV and reporting the ADRs, considering it as a professional obligation, which is similar to the previous studies that assessed the attitude of pharmacists in Saudi Arabia 16 and other countries, such as the UK and Australia 12 , 19 . Regarding PV general education, most respondents agreed that PV should be taught in undergraduate pharmacy schools in Saudi Arabia; in fact, several pharmacy schools recently added pharmacoepidemiology courses that encompass PV and medication safety to their new curricula.…”
Section: Discussionsupporting
confidence: 85%
“…The participants were recruited using convenience sampling as it was the most appropriate approach to enroll HCWs, in terms of the feasibility, practicality and availability of HCWs during the COVID-19 pandemic, considering the restrictions and most HCWs working shifts [ 111 , 112 ]. Participant recruitment continued until the minimum required sample size at each of the hospitals was attained.…”
Section: Methodsmentioning
confidence: 99%
“…They are not just focused on dispensing medications but also providea wide range of services such as MTM, health education, preventive care, immunizations, and patient counseling. By actively engaging with patients, community pharmacists contribute significantly to the overall healthcare system by offering accessible and holistic care [ 69 ]. Typically, CPs are operated by either one or two pharmacists, sometimes with the assistance of a pharmacy assistant.…”
Section: Resultsmentioning
confidence: 99%